2020
DOI: 10.1155/2020/8878300
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Green Composites for Cross Arm Component in Transmission Tower: A Brief Review

Abstract: Recently, advanced technologies exploit materials from nonrenewable resources such as petroleum, natural gas, metal ores, and minerals. Since the depletion of these resources and environmental issues, it has brought attention to researchers to progress in the development of biodegradable materials from green composites. Most biofibres and biopolymers are obtained from agricultural waste products either from stem, leaf, stalk, or fruit. Nowadays, green composites with well-regulated life span have been widely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 113 publications
1
59
0
Order By: Relevance
“…Composite materials benefit over non-composite materials for possessing low weight, corrosion resistance, high fatigue power, and quick installation [ 4 , 5 ]. Composites are commonly used in the manufacture of aircraft frames, electronic devices and packaging, transmission towers, medical equipment, space vehicles, and house construction [ 6 , 7 , 8 ]. There are three types of composites: ceramic matrix composites (CMCs), polymer matrix composites (PMCs), and metal matrix composites (MMCs).…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials benefit over non-composite materials for possessing low weight, corrosion resistance, high fatigue power, and quick installation [ 4 , 5 ]. Composites are commonly used in the manufacture of aircraft frames, electronic devices and packaging, transmission towers, medical equipment, space vehicles, and house construction [ 6 , 7 , 8 ]. There are three types of composites: ceramic matrix composites (CMCs), polymer matrix composites (PMCs), and metal matrix composites (MMCs).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the A parameter of the current composite cross-arm design was higher than that of the braced cross-arm, accounting for the superior steady-state creep response of the existing design. This result indicated that retrofitting the PGFRPC cross-arm with additional braced arms would not influence the secondary stage of creep because the GFRP composite itself exhibited improved creep resistance performance [ 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Application of green technologies and materials in manufacturing is a hot topic both in the composite community and in other industries [ 373 ]. Multiple studies conducted in the last few years demonstrate that human society should do its best to thoughtfully use and recycle the products of its activity, and to minimize its carbon footprint.…”
Section: Applicationmentioning
confidence: 99%